2007
DOI: 10.1038/sj.ejhg.5201822
|View full text |Cite
|
Sign up to set email alerts
|

Communicating genetic information in families – a review of guidelines and position papers

Abstract: This article aims to review ethical and clinical guidelines and policies addressing the communication of genetic information in families. Websites of national and regional bioethics committees, national human genetics societies, international health organisations, genetic interest groups and legal recommendations committees were searched for guidelines and policies. The databases Medline, Web of Science and Google Scholar were also utilised to search for additional guidelines relating to the communication of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 22 publications
3
94
0
2
Order By: Relevance
“…8 In cases of active nondisclosure, a policy of active encouragement and persuasion characterises the professionals' role and only very rarely do professionals override their patients' confidentiality. This suggests that consultands are commonly willing to disclose genetic information to their family members, even though difficulties may be felt on how to actually communicate rather than on deciding whether they wish to inform them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In cases of active nondisclosure, a policy of active encouragement and persuasion characterises the professionals' role and only very rarely do professionals override their patients' confidentiality. This suggests that consultands are commonly willing to disclose genetic information to their family members, even though difficulties may be felt on how to actually communicate rather than on deciding whether they wish to inform them.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Although guidelines recommend that professionals should not contact family members directly, that also state that professionals should actively encourage consultands to transmit relevant risk information to relatives and support them throughout the communication process; however, there is lack of clarity regarding how this should be done. 8,9 There has been some discussion on how to cascade information about genetic health risks to the relatives of patients with familial hyper-cholesterolaemia, including the active contacting of relatives directly by professionals, although this depends entirely upon information provided by the proband. 10 With genetic diseases increasingly treatable and preventable, some recommend a more proactive role of genetic professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Although concerns about individual autonomy and privacy are either attenuated or absent in the context of post-mortem genetic testing, the results of an autopsy may be relevant to living biological relatives, with potential for third party benefit and harm (Forrest et al 2007;Semsarian et al 2015). The potential benefits of molecular autopsy may include peace of mind and early testing and treatment for biological relatives (Sexton and Metcalf 2008).…”
Section: Consentmentioning
confidence: 99%
“…There has been much debate about how health professionals should be involved with this process; the extent to which this is deemed important appears to vary according to the information that can be made available and the condition that is involved. 2,9 Two previous Australian studies have explored how professionals might assist in family communication about genetics. One study involving letters sent from the genetics service, via the proband or directly to relatives, found that there was an increase in uptake of genetic testing by relatives from 23% in the group dependent on communication by the proband to 40% in the group receiving information directly.…”
Section: Introductionmentioning
confidence: 99%